2013
DOI: 10.1111/jfpp.12132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Temperature on the Chemical Composition and Antioxidant Activity of Vaccinium Arctostaphylos Fruit and Their Jam

Abstract: Vaccinium arctostaphylos fruit (VAF) has long been an important source of food and pharmaceutical ingredients and is considered to have high antioxidant potential. Growing V. arctostaphylos in Turkey is a substantial food, but information about its antioxidant activities is scarce. Other pharmacological properties of V. arctostaphylos, specifically antioxidant activity, contents of total phenolic, total flavonoid, total anthocyanin and ascorbic acid, are also not well explored. This study was designed to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Flavonoid compounds have a structural feature of the 2-phenyl-benzopyrane or flavine nucleus, which consists of two benzene rings linked through a heterocyclic pyrane ring (Savoia 2012, Carson & Hammer 2010). Flavonoids are important plant components due to their active hydroxyl groups and anti-oxidative properties (Güder et al 2014). They are known to have antioxidant, anti-inflammatory and antitumor activity.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Flavonoid compounds have a structural feature of the 2-phenyl-benzopyrane or flavine nucleus, which consists of two benzene rings linked through a heterocyclic pyrane ring (Savoia 2012, Carson & Hammer 2010). Flavonoids are important plant components due to their active hydroxyl groups and anti-oxidative properties (Güder et al 2014). They are known to have antioxidant, anti-inflammatory and antitumor activity.…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…[7][8][9][10] Vaccinium arctostaphylos L., commonly named the Caucasian whortleberry, is the only member of the genus Vaccinium and is widely used as an antidiabetic and antihypertensive agent. 11,12 To date, this plant has been reported to contain phenolic compounds such as anthocyanin, flavanol, and procyanidins that are responsible for numerous biological activities such as reducing serum glucose concentration and improving lipid profile, antioxidant and urinary antiseptic activities, etc. 12,13 Ayaz reported that delphinidin, petunidin, and malvidin were the most predominant anthocyanins of V. arctostaphylos L. fruits, while caffeic acid and p-coumaric acid were the major phenolic compounds.…”
Section: -mentioning
confidence: 99%
“…To date, this plant has been reported to contain phenolic compounds such as anthocyanin, flavanol, procyanidins that are responsible for numerous u n c o r r e c t e d p r o o f biological activities such as reducing serum glucose concentration and improving lipid profile, antioxidant and urinary antiseptic activities etc. (12,13). Ayaz reported that delphinidin, petunidin and malvidin were the most predominant anthocyanins of V. arctostaphylos L.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccinium arctostaphylos (V. arctostaphylos) L., commonly named Caucasian whortleberry, is the only member of the Vaccinium genus and is widely used as anti-diabetic and antihypertensive agents (11,12). To date, this plant has been reported to contain phenolic compounds such as anthocyanin, flavanol, procyanidins that are responsible for numerous u n c o r r e c t e d p r o o f biological activities such as reducing serum glucose concentration and improving lipid profile, antioxidant and urinary antiseptic activities etc.…”
Section: Introductionmentioning
confidence: 99%